Réponses

2013-03-13T23:04:29+01:00
Salut ! C'est que le premier exo ?

1) 6x² - 2x - 9x + 3 + 4x² - 12x + 9
F(x) = 10x² - 23x + 12

2) f(3/2) = 10 x (3/2)² - 23 x 3/2 + 12
= 10 x 9/4 - 69/2 + 12
= 90/4 - 138/4 + 48/4
= 0
f(3/2) = 0

3) (2x -3)(2x-3 + 3x-1) =
(2x-3)(5x-4)

Voilà dis mon si il y a autre chose a faire !
2013-03-13T23:19:10+01:00
1 . F(x)= [ 2x X 3x - 2x X 1 - 3 X 3x + 3 X 1 ] + [ (2x)" au carré" + 2 X 2x X 3 - 3 " au carré" ]

= [ 36x "au carré" -2x - 9x + 3] + [ 4x "au carré" + 12x -9 ]

= 6x "au carré" -2x - 9x + 3 + 4x "au carré" + 12x -9
= 10x " au carré" + x - 6
2. 10 X (3/2" au carré" ) + 3/2 -6 ... Je te laisse calculer ..
3. F(x) = 2x -3 ( 3x - 1 + 2x - 3 )
Le 4 arrive